Optimization and mathematical modelling of surface roughness criteria and material removal rate when milling C45 steel using RSM and desirability approach / Fnides Mohamed ... [et al.] - Mohamed, Fnides Mohamed; Brahim, Fnides Brahim; Toufik, Bensana Toufik; Mohamed Athmane, Yallese (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
This work consists of studying the workability of C45 steel in face milling by using coated carbides (GC4040). The objective is to investigate the evolution of surface roughness (Ra, Ry, and Rz) and Material Removal Rate (MRR) according to cutting speed, feed rate, and depth of cut. A full-factorial design (43) was adopted in order to analyse the obtained experimental results via both Analysis of Variance (ANOVA) and Response Surface Methodology (RSM) design. The levels of cutting speed were as follows: Vc1=57 m/min; Vc2=111 m/min; Vc3=222 m/min and Vc4=440 m/min. The ranges of feed rate were fz1=0.024 mm/tooth; fz2=0.048 mm/tooth; fz3=0.096 mm/tooth and fz4=0.192 mm/tooth. As for the depth of cut levels, they included ap1=0.2 mm; ap2=0.4 mm; ap3=0.6 mm, and ap4=0.8 mm. To determine mathematical models to make predictions, a statistical analysis of the results by using RSM was applied to obtain the main effects and interactions plot of the answer. Furthermore, a multi-objective optimization procedure for minimizing Ra and maximizing the metal removed rate using the desirability approach was also implemented.